Control of three-phase grid-connected inverters under unbalanced voltage faults - Trần Quang Thọ (Journal of Technical Education Science, 2019)
Grid-connected inverters using renewable energies such as wind and photovoltaic powers are adopted very popularly with increasing capacity. Therefore, they are significantly affected when the unbalanced grid voltages occur. At that time, the negative sequences appear, traditional current controllers in grid-connected inverters usually do not consider these components. Thus, they can cause over-current of the inverters and make the power semiconductor components damage. This paper proposes a method for controlling grid-connected inverters with over-current protection under unbalanced grid voltages. The simulated results have validated the performance of the proposed method compared with that of the traditional one.